Aber die Zeit fürchtet die Pyramiden : Die Wissenschaften vom Alten Orient und die zeitliche Dimension von Kulturgeschichte - Gertzen, Thomas L. (2022)
In Europe, the bible was long used to determine the age of human civilization, supplemented by accounts written by the historians of classical antiquity. The early modern development of the natural sciences called supposed certainties into question. The classical disciplines were assigned a decisive role in this conflict. This volume presents these developments, some of them unexpected.